Pengaruh Literasi Amil terhadap Kepercayaan Muzaki Melalui Akuntabilitas dan Transparansi Amil - Avian, Ishlah; Asrori, Asrori (Universitas Negeri Semarang, 2021)
This study aims to analyze the effect of amil literacy on muzaki trust in zakat management institutions, either directly or indirectly through amil accountability and amil transparency. The population in this reaserch is manager corporate zakat on the entity in Semarang as many as 85 respondents in 20 companies that pay corporate zakat in LAZIS Jateng, LAZIS Baiturrahman and Rumah Zakat. Sampling method uses saturated sample that are 85 respondents. This reaserch uses a quantitative approach and using primary data. Data collection technique used questionnaire. Data were analyzed using descriptive analysis and path analysis. These results indicate partially only two variables, amil’s literacy and amil’s transparency are positive and significant impact to muzaki’s trust in zakat management institutions, while amil’s accountability is positive impact not significant to muzaki’s trust in zakat management institutions. Then to sobel test amil’s accountability positive mediate not significant between amil literacy to muzaki’s trust zakat management institutions. Amil’s transparency positive mediate and significant between amils literacy to muzaki’s trust zakat management institutions. The conclusion in this reaserch is amil literacy and amil’s transparency has positive and significant impact to muzaki’s trust in the LPZ, amil’s accountability is positive impact not significant to muzaki’s trust in the LPZ, amil’s accountability is positive mediate not significant between amil literacy to muzaki’s trust in the LPZ and amil’s transparency is positive mediate and significant between amil literacy to muzaki’s trust in the LPZ.